Usefulness of a TDM-Guided Approach for Optimizing Teicoplanin Exposure in the Treatment of Secondary Bloodstream Infections Caused by Glycopeptide-Susceptible Enterococcus faecium - Milo Gatti; Matteo Rinaldi; Maddalena Giannella; Pierluigi Viale; Federico Pea (Microorganisms)
To assess the clinical usefulness of teicoplanin optimized by means of a therapeutic drug monitoring (TDM)-guided approach for treating secondary bloodstream infections (BSIs) caused by Enterococcus faecium. Hospitalized patients having in the period 1 March 2021–31 October 2024 a documented BSI caused by glycopeptide-susceptible Enterococcus faecium being treated with teicoplanin as definitive targeted therapy optimized by means of a real-time TDM-guided expert clinical pharmacological advice (ECPA) program were retrospectively included. Teicoplanin trough concentrations (Cmin) ranging from 20 to 30 mg/L were defined as the desired target of efficacy based on international guidelines. Univariate analysis was performed for assessing variables potentially associated with microbiological failure (defined as persistence at the infection site of the index Enterococcus faecium strain after more than 7 days from starting treatment as documented by follow-up blood cultures). Overall, 67 patients (median age 70 years; male 55.2%) were included. Catheter-related BSIs (50.7%) and intrabdominal/biliary tract (29.9%) infections were the main sources of Enterococcus faecium BSI. The desired target of teicoplanin Cmin was attained in 62.7% of patients at the first TDM assessment and significantly increased to 85.1% (p = 0.003) at subsequent TDM-guided ECPA instances during the overall treatment course. Microbiological eradication was obtained in 95% of cases (63/67). In the univariate analysis, failing effective source control was the only variable associated with an increased risk of microbiological failure (75.0% vs. 12.7%; p = 0.01). Targeted TDM-guided teicoplanin therapy, coupled with effective source control of the primary infection site by granting microbiological eradication in the vast majority of cases, may be considered a reasonable strategy for managing glycopeptide-susceptible Enterococcus faecium secondary BSIs.